A multi-resolution filter bank and fuzzy logic based channel edge detector for military wideband radio receivers - Sumedh, Dhabu (2013)
In a typical multi-standard military radio receiver, the radio channels (frequency bands) of interest have time varying bandwidth and locations in the wideband signal. Thus the receiver needs to detect the desired channels from the wideband input signal, which involves determining bandwidths of the channels and their locations (center frequencies) within the wideband signal. In this paper we propose a multi-resolution filter bank based spectrum sensor and a fuzzy logic based algorithm for channel edge detection in the wideband signal. For the same sensing resolution, the proposed edge detector has low complexity compared to other methods available in literature. The error in channel edge detection is reduced using fuzzy logic based algorithm. Simulation results show that our method offers an average channel edge detection accuracy of 99%.